Growth performance of Cirrhinus mrigala (Ham.) fingerlings maintained on mixed feeding schedule of diets having different protein content - Saroha, R P; Garg, S K (Indian Journal of Fisheries, 2011)
Seven different mixed feeding schedules were evaluated in Cirrhinus mrigala fingerlings having mean body weight (BW) of 2.84g employing a low (L) protein (20.29%) diet and a high (H)protein (40.12%) diet, feeding @ 3% Bwd-1 for 45 days. Regular feeding for 45 days on low protein (L) diet resulted in significantly (P